Pertumbuhan Bakteri Escherichia coli dan Staphylococcus aureus Pada Media Rebusan Biji Nangka Sebagai Substitusi Media Nutrient agar - Neiny Prisy Foekh; Ulfiani Aulia Safitri (STIKes Ibnu Sina Ajibarang, 2024)
Nutrient agar (NA) is an example of a medium that is often used to grow and breed bacteria in the laboratory but has an expensive price. One of the innovations that are currently developing is by utilizing natural resources that will be used as a medium for bacterial growth at a relatively cheaper cost and easy to obtain such as Artocarpus heterophyllus seeds. This study aimed to determine whether the boiled Artocarpus heterophyllus seeds media can be used as a substitute media of Nutrient agar for the growth of Escherichia coli and Staphylococcus aureus. This study was a true experiment with a posttest-only control design and analyzed using the One-Way Anova test. The results of the one way ANOVA test showed that there was a significant difference between the boiled Artocarpus heterophyllus seeds media and the Nutrient agar on the growth of the number of Escherichia coli and Staphylococcus aureus colonies with significant values ​​of 0.006 and 0.000 (p<0.05). Based on the results of the analysis, Artocarpus heterophyllus boiled seeds media can be used as a substitute media of Nutrient agar for the growth of Escherichia coli and Staphylococcus aureus.